Detection Of Triglyceride Based On Microwave Dielectric Properties Of Triglyceride Enzymatic Reaction - Hamid, Hasnidar (2010)

(untitled)
Triglyceride is identified to have an important function in dairy products since it can cause milk rancidity and affect cheese flavor. In this study, the detection of triglyceride was done through the measurement of dielectric properties of triglyceride enzymatic reaction in the frequencies ranging from 200 MHz to 20 GHz by using Network Analyzer. This measurement is suitable to investigate the changes in dielectric properties of triglyceride and furthermore the glycerol and fatty acids formed from this reaction. The dielectric properties measured are dielectric constant, ε’ and dielectric loss, ε”. These dielectric properties are important in carrying out the investigation of molecules interaction of triglyceride as a substrate and lipase as a catalyst in the enzymatic reaction while irradiated with the electromagnetic field. This interaction can detect the presence of ionic conductivity at low frequency and also dipole orientation at high frequency of microwaves frequency range. From the interaction of triglyceride with the presence of lipase as a catalyst, the expected products obtained are fatty acids and glycerol. The glycerol and fatty acids formed from the reaction that can be seen as a cloudy upper layer liquid and a clear lower layer which can be observed after a stable condition at about 4 minutes after the reaction. By analyzing the dielectric properties of upper layer with the dielectric properties of the enzyme, a good relationship can be obtained between these values to the triglyceride concentration. For better sensitivity of the measurement, the chosen frequencies of the measurement are about 1 GHz, 2.6 GHz, 10 GHz and 15 GHz and the preferable mixing ratio between substrate and enzyme is 1:1. This condition is applied to the triglyceride and milks samples of concentration from 10000 ppm to 50000 ppm. The reading of dielectric properties was found to increase with the increasing concentration of the triglyceride and milk samples.